Ancient Function of Teneurins in Tissue Organization and Neuronal Guidance in the Nematode Caenorhabditis elegans - Topf, Ulrike; Drabikowski, Krzysztof (Frontiers in Neuroscience, 2019)
The nematode Caenorhabditis elegans expresses the ten-1 gene that encodes teneurin. TEN-1 protein is expressed throughout the life of C. elegans. The loss of ten-1 function results in embryonic and larval lethality, highlighting its importance for fundamental processes during development. TEN-1 is expressed in the epidermis and neurons. Defects in neuronal pathfinding and epidermal closure are characteristic of ten-1 loss-of-function mutations. The molecular mechanisms of TEN-1 function in neurite outgrowth, neuronal pathfinding, and dendritic morphology in C. elegans are largely unknown. Its genetic redundancy with the extracellular matrix receptors integrin and dystroglycan and genetic interactions with several basement membrane components suggest a role for TEN-1 in the maintenance of basement membrane integrity, which is essential for neuronal guidance. Identification of the lat-1 gene in C. elegans, which encodes latrophilin, as an interaction partner of ten-1 provides further mechanistic insights into TEN-1 function in neuronal development. However, receptor-ligand interactions between LAT-1 and TEN-1 remain to be experimentally proven. The present review discusses the function of teneurin in C. elegans, with a focus on its involvement in the formation of receptor signaling complexes and neuronal networks.